Сущность технологии управления организацией и ее составляющие - Мурзина, А.А.; Чернецова, Г.М. (Культура народов Причерноморья, 2014)
В статье исследуются подходы к трактовке понятий "технология управления", "методы
управления" и "инструменты управления". Анализ определений понятия «технология управления» по
ключевым словам позволил выявить три подхода к определению его сущности. Дается определение
технологии управления как совокупности взаимосвязанных управленческих процедур, обеспеченных
методами и инструментами управления, которые направлены на осуществление функций управления и
достижение целей.
Исследована связь между методами управления и инструментами управления. Установлены факторы,
влияющие на формирование технологии управления организацией. Определены задачи, которые
необходимо решить для построения эффективной технологии управления. У статті досліджуються підходи до трактування понять "технологія управління", "методи
управління" і "інструменти управління".Аналіз трактування поняття «технологія управління» за
ключовими словами дозволив виявити три підходи щодо визначення його сутності. Дається визначення
технології управління як сукупності взаємопов'язаних управлінських процедур, забезпечених методами
та інструментами управління, які спрямовані на здійснення функцій управління і досягнення цілей.
Досліджений зв'язок між методами управління і інструментами управління. Встановлені чинники, що
впливають на формування технології управління організацією. Визначені завдання, які необхідно
вирішити для побудови ефективної технології управління. The article studies the approaches to the interpretation of the terms "management technology",
"management methods" and "management instruments". The analysis of determinations of concept
«Management technology» on keywords allowed to distinguish three approach to determination of his essence:
aggregate of knowledges; sequence of operations and procedures; aggregate of methods, techniques, means.
Determination of technology of management is given as aggregate of interrelated management procedures,
provided with methods and instruments managements which are directed on realization of management
functions and achievement of aims.
The components of the technology of management are certain: management tasks, management procedures,
methods and instruments the implementation of processes and procedures.
From positions of forming of technology of management of concrete organization essence of management
method is examined in two aspects: receptions of affecting on object of management, methods of realization of
management as a type of activity. Forming the technology of management of organization implies two blocks of
of works: division the process of management onto the task and the procedure; selection of appropriate
methods and instruments of their implementation in accordance with developed concept of management
Was investigated relationship between the methods of management and management instruments. Established
the factors influencing on forming of the technology of management of organization Defined the tasks that must
be decided that effective of management technology was worked out.